2019
DOI: 10.1016/j.isprsjprs.2019.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Explanation for the seam line discontinuity in terrestrial laser scanner point clouds

Abstract: The so-called seam line discontinuity is a phenomenon that can be observed in point clouds captured with some panoramic terrestrial laser scanners. It is an angular discontinuity that is most apparent where the lower limit of the instrument's angular field-of-view intersects the ground. It appears as step discontinuities at the start (0° horizontal direction) and end (180°) of scanning. To the authors' best knowledge, its cause and its impact, if any, on point cloud accuracy have not yet been reported. This pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
(18 reference statements)
1
8
0
Order By: Relevance
“…The root mean square error (RMSE) of the best‐fitting cylinder, representing the uncertainty, and the corresponding ground‐truth pipe radius were 0.3 and 57.3 mm, respectively. The precision of the distance between the centres of the two targets, acquired from TLS, was approximately 0.1 mm, which is consistent with the sub‐millimetre centre estimation precision reported in Lichti et al (2019a). The accuracy of the estimated radius is reported for comparison.…”
Section: Experiments Designsupporting
confidence: 89%
“…The root mean square error (RMSE) of the best‐fitting cylinder, representing the uncertainty, and the corresponding ground‐truth pipe radius were 0.3 and 57.3 mm, respectively. The precision of the distance between the centres of the two targets, acquired from TLS, was approximately 0.1 mm, which is consistent with the sub‐millimetre centre estimation precision reported in Lichti et al (2019a). The accuracy of the estimated radius is reported for comparison.…”
Section: Experiments Designsupporting
confidence: 89%
“…A circular patch around each target was manually extracted from the point cloud. The centre coordinates were estimated using the method described by Lichti et al (2019b). Past experience with this instrument has demonstrated that millimetre-level 3D coordinate accuracy can be achieved in a similar environment with comparable dimensions (Lichti et al, 2019a).…”
Section: Accuracy Assessmentmentioning
confidence: 99%
“…From the figures, it is known that the increments of random noises from 0 to ±8 mm do not lead to large increases in the RMSEs. Results of scanner calibrations published recently [27][28][29][30][31] indicated that the point cloud errors are normally less than 8 mm within a scan range of 10 m. As a result, it is deduced that the proposed model can work well with half of the joint scanned from a single scan. The RMSE of the translational, rotational, and dimensional parameters for Joint (a) from 10° to 360° coverage and from noise level 0 mm to ± 8 mm is shown in Figures 12, 13, and 14, respectively.…”
Section: Accuracy Analysismentioning
confidence: 94%